Identifying cell class specific losses from serially generated electroretinogram components. - Nguyen, Christine T O; Vingrys, Algis J; Wong, Vickie H Y; Bui, Bang V (BioMed Research International, 2013)
Purpose. Processing of information through the cellular layers of the retina occurs in a serial manner. In the electroretinogram (ERG), this complicates interpretation of inner retinal changes as dysfunction may arise from "upstream" neurons or may indicate a direct loss to that neural generator. We propose an approach that addresses this issue by defining ERG gain relationships. Methods. Regression analyses between two serial ERG parameters in a control cohort of rats are used to define gain relationships. These gains are then applied to two models of retinal disease. Results. ThePIIIamp to PIIamp gain is unity whereas the PIIamp topSTRamp andPIIamp to nSTRamp gains are greater than unity, indicating "amplification" (P < 0.05). Timing relationships show amplification between PIIIit to PlIit and compression for PIIit topSTRit and PIIit to nSTRit, (P < 0.05). Application of these gains to w-3-deficiency indicates that all timing changes are downstream of photoreceptor changes, but a direct pSTR amplitude loss occurs (P < 0.05). Application to diabetes indicates widespread inner retinal dysfunction which cannot be attributed to outer retinal changes (P < 0.05). Conclusions. This simple approach aids in the interpretation of inner retinal ERG changes by taking into account gain characteristics found between successive ERG components of normal animals.